Non‐destructive detection of coconut quality using RF sensor. Issue 19 (1st September 2020) - Kumar Varshney, A.; Pathak, N.P.; Sircar, D.
Abstract : This Letter proposes the application of RF technology for the non‐destructive detection of spoiled coconut at the pre‐processing stage. Since the dielectric property of coconut water changes at different stages of coconut, the sensor measures the content of water inside a coconut sample non‐destructively at 2.45 GHz. The sensor has been trained to determine the threshold water level between healthy and spoiled coconut which in turn can be used to sort the coconuts. The measurement results have been presented for different processing stages of coconut for different samples. Detecting coconut quality through dielectric sensing reveals some very impressive results and opens the doors for better consumption.